Investigating the body self-relationship in young Black South African women. - Shelembe, Thulisile Buhle (My University, 2014)
The purpose of this research was to investigate contemporary conceptions of beauty and bodily modificatory behaviour of young, Black, South African women. In a society where a lot of emphasis has been placed on a woman’s physical appearance, it was important to determine how these young women feel about their bodily appearance and if whether this is influenced by their social milieu. Constructions of beauty are largely constructed around White womanhood, thus Black women might feel marginalised by the White majority’s Western beauty standards. Data for this research report was collected by conducting semi-structured interviews with six female, Black South African, first year psychology students at the University of the Witwatersrand. The participants received a 1% incentive for their participation which contributed to their end of semester mark. The findings of the study show that conformity to Western standards of beauty has a negative bearing on the participants perceptions of how they feel about their bodies. The media has also become influential in changing perceptions of beauty within Black South African contemporary culture. Salient features of beauty, such as hair and skin colour seem to be embedded in the historical processes of oppression.
Keywords: Body image in women--South Africa.; Women, Black--South Africa.; Beauty culture--South Africa.; Feminine beauty (Aesthetics)--South Africa.